Geotechnical Engineering Advances in Soil Mechanics and Foundation Engineering - Hemeda, Sayed; Barış Can Ülker, Mehmet (IntechOpen, 2020)
This book discusses contemporary issues related to soil mechanics and foundation engineering in earthworks, which are critical components in construction projects and often require detailed management techniques and unique solutions to address failures and implement remedial measures. The geotechnical engineering community continues to improve the classical testing techniques for measuring critical properties of soils and rocks, including stress wave-based non-destructive testing methods as well as methods used to improve shallow and deep foundation design. To minimize failure during construction, contemporary issues and related data may reveal useful lessons to improve project management and minimize economic losses. This book focuses on these aspects using appropriate methods in a rather simple manner. It also touches upon many interesting topics in soil mechanics and modern geotechnical engineering practice such as geotechnical earthquake engineering, principals in foundation design, slope stability analysis, modeling in geomechanics, offshore geotechnics, and geotechnical engineering perspective in the preservation of historical buildings and archeological sites. A total of seven chapters are included in the book.